Roles of Thailand’s National Theater for Safeguarding National Intangible Cultural Heritage - Permsin, Sasithorn; Watanasawad, Kriengkrai (Mahachula Academic Journal, 2021)
This study explored the role and management of Thailand’s National Theatre as well as suggested guidelines for safeguarding national intangible cultural heritage. The data collection employed mixed methods, including; observation, in-depth interviews, questionnaires, and satisfaction survey. The research participants were executives, scholars who have expertise in performing arts and theatre management, and 400 Thai and foreign audiences who had experienced watching the show at the National Theatre. The research results reviewed that management resources of Thailand’s National Theatre include six key elements, which are (1) man, (2) money, (3) material, (4) method, (5) management, and (6) machine. In addition, the Theatre provided a range of performances to promote the intangible cultural heritage to the public, including; (1) Khon, (2) Lakorn, (3) Thai classical music, (4) Occidental music, and (5) other special programs. Therefore, Khon, also known as a masked dance drama, was the most popular performance to the audiences and their overall satisfaction toward the National Theatre was significantly high. The research implications guide the management of the National Theatre that its work procedures should be constructively established, in line with the vision and mission of the Fine Arts Department. Moreover, the target market should be analysed in order to formulate an efficient strategic plan, followed by the practical evaluation for internal quality improvement. In term of cultural dissemination and development, more information about the performances and the Theatre should be provided and be accessible to every group of the audiences.